Analysis of Public Service Innovation "Sama Thukel" by the Regional Revenue Agency of Maluku Province - Wailussy, Vivin Faidar; Rengifurwarin, Zainal Abidin; Patty, Julia Theresia (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This research aims to analyze the public service innovation "Sama Thukel" implemented by the Regional Revenue Agency of Maluku Province. Public service innovation is a critical element for improving the quality of governance and enhancing the public's trust in government institutions. "Sama Thukel" is a digital-based public service innovation designed to facilitate taxpayers' access to regional tax services, ensuring efficient and transparent processes. Through qualitative methods, including interviews and document analysis, the study explores the design, implementation, challenges, and impact of this innovation on taxpayers and the agency itself. The findings reveal that the "Sama Thukel" program has significantly improved taxpayer compliance, reduced bureaucratic inefficiencies, and created a more transparent and accountable system. However, challenges remain in terms of digital literacy and the need for continuous system upgrades. This research highlights the importance of adapting public service innovations to local contexts and the role of technology in enhancing governance. The study concludes by offering recommendations for optimizing the "Sama Thukel" program and ensuring its sustainability.